(3SHd JMbjb GdYdGbI GdJHGOdjI Hjf GdeOGQS GdeSJOGeI h GdHjFI GdeMjWI ai VhA JQTjO GdWGbI (B/ s - (3NGdO gTGe eMehO GHQGgje ageis; (3JGeQ eMeO YHOGdYRjR YeQh (B: s; (3eMeO QVG YHOGddg (B: s ((3GdbGgQI (B: s (3NGdO gTGe eMehO GHQGgje agei (B: s, 2013)
(3JYJHQ GdeOGQS eQHjI GdCLjGd Ydi GdYde h Gdbje (B: (3ceG gi fhGI GdeLJeYGJ (B: (3dPG cGf ef Gdege EdbGA GdVhA Ydi GdeOGQS h SHd JMbjb eHGOF GdGSJOGeI aj GdJUeje GdeYeGQj h GdYeQGfj dgG dJchf fhGI GdJCKjQ aj GdeLJeY fMh JfejI GdYeQGf h GSJOGeI GdHjFI h GdWGbI (B: (3MjK JgOa GdeOGQS GdeSJOGeI Edi QaY eSJhi GdhYj GdHjFj hSW bWGY GdWdGH h GdeYdejf djfJTQ HYO Pdc OGNd GdeLJeY h Pdc ef NdGd GdeeGQSGJ GdHjFjI GdGjLGHjI GdJj JgOa Edi Jbdjd GdJCKjQGJ GdSdHjI Ydi GdHjFI h HGdCNU aj eLGd GdejGg h GdWGbI h GdghGA h GdfaGjGJ h JMbjb GdGSJOGeI ai cGaI GdeLGdGJ (B( (3GdHjFjI (B: (3GdeLJeYjI (B: (3GdGbJUGOjI (B) (3Ydi eSJhi GdMQe GdeOQSi h GdHjFI GdeLJeYjI GdeMjWI Hg eeG jNdb eLJeY eSJOGes
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdgfOSI (B- (3bSe GdgfOSI GdeYeGQjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdGSJOGeI h eaGgjegG s; (3GdWGbI h CfhGYgG s; (3GdeYGjjQ GdJUejejI ddeOGQS GdeSJOGeI s